Manajemen Tempat Pengelolaan Sampah Terpadu (TPST) di Desa Cilongok Kabupaten Banyumas - Rahmansyah, Arif; Pribadi, Indah Ayu Permana; Amanda, Ariesta; Sutikno, Chamid; Millata, Chanifia Izza (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
Effective and sustainable waste management has become a major challenge in Cilongok Village, Cilongok District, due to the high volume of domestic waste generated by the community. This study aims to design integrated waste management facilities (TPST) as a solution to reduce environmental impacts and raise public awareness about waste management. The research employs a qualitative methodology, with data collected through observations, interviews, and documentation, and informants selected using purposive sampling. The study results are analyzed from the following aspects: Planning: The planning process involves several strategies or stages, including work program planning, socialization planning, and development planning. Organization: A structured organization and a clear division of roles and responsibilities have been established within the waste management institution. Implementation: Flagship programs have been executed, such as compost production, RDF (Refuse-Derived Fuel) manufacturing, and maggot feed production from waste slurry. Supervision: Supervision activities include internal monitoring among TPST members and external involvement, particularly from village government authorities.